'Situational Analysis' and Economics: an attempt at clarification. (14th January 2019) - Palacio-Vera, Alfonso
Abstract: Popper's 'Situational Analysis' (SA) constitutes his methodological proposal for the social sciences. We claim that the two hallmarks of SA are: (i) that scientists assume they possess a 'wider' view of the problem-situation than actors do, and (ii) use the model as an ideal 'benchmark' scenario to identify the deviation of actors' actual behaviour from the former. We argue that SA is not a generalization of the neoclassical theory of individual behaviour but captures instead the methodology adopted by modern behavioural economists. Last, we argue that SA highlights a way of acquiring knowledge that has gone unnoticed in the literature.